2019
DOI: 10.3390/jcm9010050
|View full text |Cite
|
Sign up to set email alerts
|

Application of Impedance-Based Techniques in Hepatology Research

Abstract: There are a variety of end-point assays and techniques available to monitor hepatic cell cultures and study toxicity within in vitro models. These commonly focus on one aspect of cell metabolism and are often destructive to cells. Impedance-based cellular assays (IBCAs) assess biological functions of cell populations in real-time by measuring electrical impedance, which is the resistance to alternating current caused by the dielectric properties of proliferating of cells. While the uses of IBCA have been widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 73 publications
(114 reference statements)
0
16
0
Order By: Relevance
“…The documented research applications of RTCA include the toxicological studies, specifically the research on myocardial toxicity [37], and the screening of the toxicity of engineered nanoparticle bio-conjugates [38]. Furthermore, the RTCA application was reported in the hepatological field [39], as well as in traditional Chinese herbal medicine [40].…”
Section: Acea Xcelligence ® Real-time Cell Analysis (Rtca)mentioning
confidence: 99%
“…The documented research applications of RTCA include the toxicological studies, specifically the research on myocardial toxicity [37], and the screening of the toxicity of engineered nanoparticle bio-conjugates [38]. Furthermore, the RTCA application was reported in the hepatological field [39], as well as in traditional Chinese herbal medicine [40].…”
Section: Acea Xcelligence ® Real-time Cell Analysis (Rtca)mentioning
confidence: 99%
“…Morgan et al described the potential of impedance-based techniques in hepatology research and have identified the main platforms used for impedance-based cell analysis with hepatocytes in monolayer cultures in vitro. The application of these techniques in vitro and ex vivo to 3D structures still needs to be addressed and would be an important breakthrough [ 7 ]. Previous work on the electrical characterization of hepatic tissue has focused on cancerous tissue [ 8 ] or liver steatosis [ 9 , 10 ], while liver fibrosis has been less explored.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, DS is a non-invasive, fast, and promising method for cell screening. DS has been widely used for impedance measurements of yeast cells [10][11][12], breast cancer cells [13], lymphocyte activation profiling [14], monitoring performance of epithelial tissues [15], and hepatology research [16].…”
Section: Introductionmentioning
confidence: 99%